ANALISA KEBUTUHAN RUANG PARKIR DI PASAR MUARA RUMBAI PASIR PENGARAIAN - Pada Lumba; Syahroni - (Universitas Pasir Pengaraian, 2011)
Parking problem at Muara Rumbai Market is there are no special place to parking, just used the street around the market. And the consequently, visitor will park they vehicle at the street, that will constricting the street. If this not anticipate from now on, will make traffic jam at the street. To solving this problem, have to do some analysis for parking problem around the market.This research use survey method, which place some surveyor at the parking location around the market at the peak hour to recording the vehicle license plate numbers of motorcycles and passenger cars at the survey form for 4 hours with 5 minutes interval. From the data carried out, analyze how much parking accumulate, parking indexes and turn over at the parking location.From the analysis can found that the accumulate parking is passenger cars with 41 vehicles and 296 motorcycles. The low number of turn over passenger cars are couse by the most vehicle parking at this market is belong to marketeer. The turn over number of the motorcycles is 1.2 motorcycle/parking lot, this show the parking lot use by motorcycle is high enough